Poly (ADP) ribose polymerase inhibition: A potential treatment of malignant peripheral nerve sheath tumor. Issue 2 (1st February 2016) - Kivlin, Christine M.; Watson, Kelsey L.; Al Sannaa, Ghadah A.; Belousov, Roman; Ingram, Davis R.; Huang, Kai-Lieh; May, Caitlin D.; Bolshakov, Svetlana; Landers, Sharon M.; Kalam, Azad Abul; Slopis, John M.; McCutcheon, Ian E.; et al.
ABSTRACT: Poly (ADP) ribose polymerase (PARP) inhibitors, first evaluated nearly a decade ago, are primarily used in malignancies with known defects in DNA repair genes, such as alterations in breast cancer, early onset 1/2 ( BRCA1/2 ). While no specific mutations in BRCA1/2 have been reported in malignant peripheral nerve sheath tumors (MPNSTs), MPNST cells could be effectively targeted with a PARP inhibitor to drive cells to synthetic lethality due to their complex karyotype and high level of inherent genomic instability. In this study, we assessed the expression levels of PARP1 and PARP2 in MPNST patient tumor samples and correlated these findings with overall survival. We also determined the level of PARP activity in MPNST cell lines. In addition, we evaluated the efficacy of the PARP inhibitor AZD2281 (Olaparib) in MPNST cell lines. We observed decreased MPNST cell proliferation and enhanced apoptosis in vitro at doses similar to, or less than, the doses used in cell lines with established defective DNA repair genes. Furthermore, AZD2281 significantly reduced local growth of MPNST xenografts, decreased the development of macroscopic lung metastases, and increased survival of mice with metastatic disease. Our results suggest that AZD2281 could be an effective therapeutic option in MPNST and should be further investigated for its potential clinical use in this malignancy.